The Effect of Earnings Recognition on Firm-Specific Information Variation - Park, Ji-Hye; Cho, Joong-Seok (International Journal of Economics and Financial Issues, 2016)
We examine the relation between earnings recognition practices and firms’ information environment. Using a sample of U.S. firms over the period 2000-2012, we investigate how earnings timeliness and smoothness affect firm information environment. To measure firms’ information environment, we adopt stock return synchronicity. The timeliness of earnings recognition measures the extent to which current earnings reflect value-relevant information into stock prices. As managers use earnings smoothing as a vehicle to reveal their private information, we expect earnings smoothing improves earnings informativeness and enables the market to incorporate more firm-specific information. Our study shows that as earnings timeliness increases, the market incorporates more firm-specific information into stock prices. In addition, as a firm’s earnings become more volatile (less smooth), such a firm’s stock return reflects more market-wide variation relative to firm-specific information. Keywords: Earnings smoothing, Timeliness, Stock return synchronicity, U.S.A. JEL Classifications: G14, M41